Genetic epidemiology of pharmacogenetic variations in CYP2C9, CYP4F2 and VKORC1 genes associated with warfarin dosage in the Indian population. (July 2014) - Giri, Anil K; Khan, Nazir M; Grover, Sandeep; Kaur, Ismeet; Basu, Analabha; Tandon, Nikhil; Scaria, Vinod; Consortium, IGV; , INDICO; Kukreti, Ritushree; Brahmachari, Samir K; Bharadwaj, Dwaipayan
Aim: Warfarin, a widely used anticoagulant, exhibits large interindividual variability in dose requirements. CYP2C9 and VKORC1 polymorphisms in various ethnic groups have been extensively studied as genetic markers associated with variable drug response. However, allele frequencies of these variants have not been assessed in major ethnic groups in the Indian population.Materials & methods: To study the functional variants known to affect warfarin dosing, we reanalyzed genotype microarray datasets generated as a part of genome-wide association studies as well as data from the Indian Genome Variation database. We examined data from 2680 individuals across 24 ethnically diverse Indian subpopulations.Results: Allelic distribution of VKORC1 (-1639G>A) showed a greater degree of variation across Indian subpopulations, with frequencies as low as 6.5% in an out-group subpopulation to >70% in Tibeto–Burmans. Risk allele frequency of CYP4F2*3 (V433M) was higher in north Indians (0.30–0.44), as compared with other world populations, such as African–American (0.12), Caucasian (0.34) and Hispanic (0.23). The VKORC1 variant (-1639A) was shown to be prevalent amongst Tibeto–Burmans, whereas CYP2C9 (R144C, I359L) and CYP4F2 (V433M) variants were observed in considerable variability amongst Indo–Europeans. The frequency of CYP2C9*3 (I359L) in north Indians was found to be higher than in most Asian populations. Furthermore, geographical distribution patterns of these variants in north India showed an increased trend of warfarin extensive metabolizers from the Himalayan to Gangetic region. Combined allele frequency ( CYP2C9*3 and CYP4F2*3 ) data suggest that poor metabolizers varied in the range of 0.38–1.85% in Indo–Europeans.Conclusion: Based on genotypic distribution, the majority of the Indian subpopulation might require higher doses for stable anticoagulation, whereas careful assessment is required for Tibeto–Burmans who are expected to have intermediate dose requirement. This is the largest global genetic epidemiological study examining variants associated with warfarin that could potentially be valuable to clinicians in optimizing dosage strategies. Original submitted 4 April 2014; Revision submitted 23 May 2014